Simple Multi-Element Solid Phase Extraction Procedure to Determine Some Heavy Trace Metals in Honey by Flame Atomic Absorption Spectrometry - Antakli, Saad; Alahmad, Akram; Zaher El-Beck, Abdallah (Asian Journal of Chemistry, 2011)
A multi-element solid phase extraction procedure on C18ec and C6H5 modified silica cartridges and flame atomic absorption spectrometric determination of some heavy metals in honey samples is proposed. Manufacturing of a simple handmade solid phase extraction stand has also been illustrated in this work. The influences of analytical parameters including pH, eluent composition and sample volume, etc., on the recoveries of copper, iron, manganese, nickel and zinc were investigated. The interfering effects of some common coexisting cations on the retentions of the analytes were also examined. The recoveries of analytes were generally higher than 95 % for both phases. The developed methods were applied to the determination of metal ions in 25 Syrian honey samples from different botanical and geographical areas. The accuracy of samples' results was compared by GF-AAS determination.